Health Management of Working Pregnant Nurses: A grounded theory study - Marie Hino; Risa Takashima; Rika Yano (Wiley, 2024)
Abstract Aim To explore the recognition of pregnant nurses on how they managed their health conditions to examine safe working strategies. Design A qualitative study with a grounded theory approach. Methods Twenty‐one nurses engaged in work during their pregnancy were recruited and interviewed using a semi‐structured questionnaire from January to June 2021. The data were analysed using a constant comparative method. Results The core category 'duelling roles' and the four other categories emerged. Pregnant nurses understand the 'weight of one' of being a professional in the workplace. Therefore, despite their health concerns, they struggle to complete their work as one team member to avoid inconveniencing others. However, through experiencing various nursing situations, they 'perceive one's limits' of working as they had done before pregnancy and protect their health and patients. Nevertheless, interactions with patients and their colleagues bring 'delight in nursing', which encourages them to continue working. Pregnant nurses thus develop a 'prioritizing the foetus' working style to continue being nurses while protecting their health. Implications for the Profession and/or Patient Care These results provide meaningful guidance in considering safe job retention strategies for pregnant nurses. Sharing and developing the 'prioritizing the foetus' mindset and management skills gained by the participants may be beneficial for the appropriate health management of pregnant nurses. The study may also facilitate nursing managers' understanding of the experiences of pregnant nurses and encourage them to consider reviewing nursing practices. Reporting Method The Consolidated Criteria for Reporting Qualitative Studies checklist was used to ensure the quality of research reporting. Patient or Public Contribution Members of the nursing team were involved in the design, conduct and interpretation of the data in this study.